Carbon Paste Electrochemical Sensors for the Detection of Neurotransmitters - Rejithamol, R.; Beena, S. (Frontiers in Sensors, 2022)
The relevance of the carbon-paste electrodes in the field of neurotransmitter electrochemical sensing is focused in this review. The significance of biomolecules especially neurotransmitters in treatments related to different diseases has tremendously expanded the scope of analytical detection of these biomolecules. The detection of them from biological fluids and pharmaceutical dosages are highly recommendable because the normal functioning of a human body very much related to the exact concentrations of these biomolecules. Therefore, electro analytical techniques can be employed for the quantification of these molecules as these techniques take over the advantage of fast response time, easy to handle and possess highly sensitive results. Due to the cost-effectiveness and vague electron transfer kinetics, a large number of carbon-paste electrode based electrochemical sensors have been developed for various biomolecules, environmental pollutants, food additives and pharmaceuticals. This review gives an intuition on different materials used for the quantification of the neurotransmitters using carbon-paste electrode modified electrochemical methods. The electrochemical analysis of neurochemicals by probing the various analytical utilities of carbon-paste electrodes can enlighten the upcoming research on these molecules.